(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The term gray markets refer to the offer of certifiable trademarked items through appropriation channels unapproved by the maker or brand proprietor. No less than three circumstances may make motivating forces to import gray market merchandise currency fluctuations, manufacturing and price contrasts amongst countries, and status based consumption of branded goods at low price. This review paper is an attempt to understand the gray market, first copy products, identifying the difference between first copy and genuine products, and buyers attitude towards gray market products. This understanding will help the genuine distributer to find some ways to bloc gray market transactions by some strategies which discussed in the end part of this paper.